BIOFILM-INDUCED GINGIVAL DISEASES - Soares, Kaio Henrique; Martins, Olga Beatriz Lopes; Leite, Mariana Botelho; Alves, Sâmia Francy Ferreira; Lopes, Maria Rita Lima; Santos, Jefferson Aguiar; Paulino, Gabriela Leite; Soares, Célio Leone Ferreira (Seven Editora, 2026)
This chapter addresses biofilm-induced gingival diseases, highlighting gingivitis as the initial and reversible manifestation of periodontal inflammation, characterized by the absence of clinical attachment loss. The biological mechanisms involved in the inflammatory response to dental biofilm are discussed, including the participation of cytokines, prostaglandins, and metalloproteinases. The text also explores the developmental stages of gingivitis, the new 2017 classification of periodontal diseases, and the main systemic, pharmacological, and local factors that can modify the gingival response. Furthermore, it differentiates biofilm-induced gingival diseases from non-plaque-induced conditions, reinforcing the importance of early diagnosis and biofilm control for the prevention of periodontal progression.